2018
DOI: 10.1016/j.ijnss.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

An mHealth intervention to improve medication adherence among patients with coronary heart disease in China: Development of an intervention

Abstract: Objectives With this study, we aimed to develop a mobile technology (mHealth) intervention to improve medication adherence among patients with coronary heart disease (CHD). Methods The study was conducted in two phases with CHD patients from a Cardiology Department of a hospital located in China. Each phase was independent from the other. Phase 1 tested the integration of the two apps — “WeChat” and “BB Reminder” — as an mHealth intervention. All participants received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(94 citation statements)
references
References 15 publications
(12 reference statements)
1
91
0
2
Order By: Relevance
“…Patients’ lack of follow-up care may also be related to the healthcare system in China. The included studies did not provide direct evidence to support this point, but empirical evidence from other studies has shown that patients with CHD prefer to use hospitals rather than local primary healthcare clinics for treatment 48. Under the current system, most physicians in large hospitals are required to see a great number of patients each day, and they may not have a sufficient amount of time to provide advice to patients on medication adherence.…”
Section: Discussionmentioning
confidence: 98%
“…Patients’ lack of follow-up care may also be related to the healthcare system in China. The included studies did not provide direct evidence to support this point, but empirical evidence from other studies has shown that patients with CHD prefer to use hospitals rather than local primary healthcare clinics for treatment 48. Under the current system, most physicians in large hospitals are required to see a great number of patients each day, and they may not have a sufficient amount of time to provide advice to patients on medication adherence.…”
Section: Discussionmentioning
confidence: 98%
“…However, their survey results showed that communication effectiveness significantly influenced the adoption of SMS but did not have a significant effect on perceived usefulness. Nevertheless, researchers [7,8] indicated that communication effectiveness facilitates interactions between people and health care providers, thus influencing perceived usefulness and people's intention to use mHealth. Thus, we posit that: Trustworthiness is another major contextual issue as information and communications technologies become ubiquitous and pervasive [44,45].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In the US, around one third of cell phone users have accessed health information, including behavioral health issues, frequently using mobile devices [5,6]. In China, mHealth has been used to improve communications between patients and health care providers, promote public health awareness and health education, and enhance the efficiency of medical services and public health campaigns [7,8]. mHealth is becoming more and more important because China's number of mobile Internet users has increased from 346 million in 2011 to 817 million in 2018 [9,10], and the number of active mHealth users was 466 million in the first quarter of 2019 [11].…”
Section: Introductionmentioning
confidence: 99%
“…This study involved 33 patients with cardiovascular disease with SaltSwitch Intervention and 33 participants in the control group, showing no significant difference as evidenced by the statistical results (P > 0.05) [15]. In contrast to a research conducted by Chen S, 2018 [13].…”
Section: Dietmentioning
confidence: 75%
“…Phase 2: Material on health education was given every five days and reminders to take medicine were given every day. The results showed that there was an increase in medication adherence of the participants [13].…”
Section: B Compliance With Medicationmentioning
confidence: 89%